Teaching Load and Project-Based Learning: Unveiling the Effects on Teacher Performance and Compensation - amir, Amir; Wisudaningsih, Endah Tri; Zaini, Abdul Wahid; Hefniy, Hefniy (JURNAL AL-TANZIM, 2025)
This study investigates how teaching load and implementing project-based learning (PBL) models influence teacher performance, specifically focusing on the mediating role of work compensation. Despite the increasing adoption of PBL in classrooms, limited research has examined its direct and indirect effects on educators themselves. Using a quantitative survey approach, data were collected from 300 teachers across several schools in Probolinggo Regency. The research employed Structural Equation Modeling (SEM) through SmartPLS to analyze direct and mediated relationships between the variables. Findings reveal that teaching load has a significant positive effect on both work compensation and teacher performance, whereas the direct impact of PBL on performance is statistically insignificant. However, PBL positively influences compensation, significantly contributing to performance improvement. These results suggest that compensation mechanisms are crucial in translating instructional innovations and workload demands into tangible improvements in teacher outcomes. The study underscores the importance of aligning institutional compensation policies with workload realities and pedagogical strategies to foster a more effective and motivated teaching workforce. The findings offer practical implications for educational stakeholders seeking to improve teacher performance through a balanced consideration of workload, compensation, and teaching methodology.